Weather radars – the new eyes for offshore wind farms?. (16th August 2013) - Trombe, Pierre‐Julien; Pinson, Pierre; Vincent, Claire; Bøvith, Thomas; Cutululis, Nicolaos A.; Draxl, Caroline; Giebel, Gregor; Hahmann, Andrea N.; Jensen, Niels E.; Jensen, Bo P.; Le, Nina F.; Madsen, Henrik; et al.
ABSTRACT Offshore wind fluctuations are such that dedicated prediction and control systems are needed for optimizing the management of wind farms in real‐time. In this paper, we present a pioneer experiment – Radar@Sea – in which weather radars are used for monitoring the weather at the Horns Rev offshore wind farm, in the North Sea. First, they enable the collection of meteorological observations at high spatio‐temporal resolutions for enhancing the understanding of meteorological phenomena that drive wind fluctuations. And second, with the extended visibility they offer, they can provide relevant inputs to prediction systems for anticipating changes in the wind fluctuation dynamics, generating improved wind power forecasts and developing specific control strategies. However, integrating weather radar observations into automated decision support systems is not a plug‐and‐play task, and it is important to develop a multi‐disciplinary approach linking meteorology and statistics. Here, (i) we describe the settings of the Radar@Sea experiment, (ii) we report the experience gained with these new remote sensing tools, (iii) we illustrate their capabilities with some concrete meteorological events observed at Horns Rev and (iv) we discuss the future perspectives for weather radars in wind energy. Copyright © 2013 John Wiley & Sons, Ltd.